THE ANALYSIS OF SPEECH ACT IN â€œBARBIE AS RAPUNZELâ€ MOVIE - Hunsawati, Siti; Rohamana, Rohmana; Siam, Siam (Universitas Halu Oleo, 2019)
This thesis is about the analysis of speech act in Barbie as Rapunzel movie. The research questions of this thesis were (1) what are the direct and indirect speech acts used by the main character in Barbie as Rapunzel movie? And (2) What are the perlocutionary acts of the main characterâ€™s utterances in Barbie as Rapunzel movie?. The objectives of this research were (1) To decribe the direct and indirect speech acts used by the main character in Barbie as Rapunzel Â movie Â andÂ (2) Â To Â describe Â the perlocutionary actsÂ Â ofÂ Â theÂ Â mainÂ Â characterâ€™sÂ Â utterancesÂ Â inÂ Â BarbieÂ as Rapunzel movie. This research used a qualitative method to describe and analyze Â the Â utterance. Â The Â technique Â ofÂ data Â collection were (1) The researcher download Barbie as Rapunzel movie on youtube. (2) The researcher watched the movie of Barbie as Rapunzel Â repetedly. (3) Reading and checking dialogue which related with research from the movie script â€œBarbie as Rapunzelâ€ movie. (4) The researcher classified the dirrect, indirect speech, and perlocutionary acts. The techniqueÂ Â ofÂ Â dataÂ Â analysisÂ Â wereÂ (1)Â Â TheÂ Â researcher identified the direct, indirect speech act and perlocutionary acts from Barbie as Rapunzel movie. (2) Described and analized the utterances which include direct, indirect, and perlocutionary acts. (3) Concluding the data analysis. The result of this thesis show that direct speech acts is the dominant types of speech acts. Where, there are 58 direct speech acts, 2 indirect speech acts, and 41 perlocutionary acts.Â Keywords:Â Speech Act, Movie